Time and Cost Analysis Using the Critical Chain Project Management Method in the Retrofitting Work of the East Java Province Human Rights Office Building into a Green Building - Aji Sasongko, Christio; Teki Tjendani, Hanie; Wulandari, Esti (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The retrofitting work of the East Java Province Public Works Office Building into a Green Building encountered several obstacles during the construction process that caused delays in the execution of the work. Therefore, scheduling control is needed using the Critical Chain Project Management method. CCPM aims to manage scheduling design and process control by concentrating on eliminating multitasking, Parkinson's Law, and student's syndrome, which have been considered to cause suboptimal field work execution time and increased waste in terms of time. CCPM also has a buffer mechanism used in scheduling as a tool to protect project schedules from uncertainty, ensuring that every task can be completed on time. By using the Critical Chain Project Management method, a project buffer value of 26 days and a feeding buffer of 11 days were obtained, so that the original work duration of 180 days would become 143 days if the entire buffer of 37 days was not applied. The implementation cost with a value of Rp. 32,048,830,700 can be more efficient at Rp. 30,584,593,995 if the entire buffer is not used, with a project buffer saving of Rp. 1,028,923,090 and feeding buffer savings of Rp. 435,313,615, resulting in a total work cost savings of Rp. 1,464,236,705.